Suicidio y violencia de género : sobre una idea de Enriqueta Chicano / Miguel Lorente Acosta, Cruz Sánchez de Lara Sorzano, Covadonga Naredo Camblor - Sánchez de Lara Sorzano, CruzNaredo Camblor, Covadonga; Lorente Acosta, Miguel
Bibliografía: p. 133-146